Pengaruh Media Sosial Tiktok terhadap Numerasi Siswa - Septian, Ari; Nursofa, Wina (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2025)
This research aims to determine the influence of social media Tiktok on the numeracy of class VII junior high school students. In this research, it consists of the independent variable, namely the use of social media Tiktok (X) and the dependent variable, namely student numeracy (Y). This research uses quantitative research methods with a cross-sectional survey design and the research instrument uses numeracy essay test questions and non-tests in the form of a questionnaire on the use of social media Tiktok. The population in this study were all class VII students of SMP PGRI 1 Cianjur for the 2023-2024 academic year, with samples taken using purposive sampling, namely 23 students or 46% of the total students. Data analysis techniques in this research are descriptive statistical tests, normality tests, linearity tests, homoscedasticity tests, anova tests and simple linear regression tests. Based on the results of quantitative data analysis using the JASP program version 0.16.3.0, it was concluded that there was an influence of social media Tiktok on the numeracy of class VII SMP students. The influence of using social media Tiktok on students' numeracy can have a positive effect if used well, for example for studying, and conversely it can have a negative effect if used for bad purposes.